(untitled) (Laisvalaikio tyrimai, 2021)
Relevance. The relevance of the study lies in the fact that 2020, the year of the pandemic, became a turning point for many areas of the national economy, and the tourism industry was no exception. Due to the closure of borders between countries, International Tourism was dropped dramatically. In the context of the COVID-19 pandemic, it is necessary to refocus on growing outbound tourist flow to the development of domestic tourism; accordingly, it is necessary to be ready to meet the needs of foreign and domestic tourists in the territory of the Republic of Kazakhstan. Kazakhstan can surprise tourists with its rich natural resources, minerals, mountainous and recreational areas, and natural parks as well. State national parks are important for the conservation and sustainable use of biological diversity in the Republic of Kazakhstan. These days the Government is paying great attention to the formation of effective development of natural parks, as well as the development of tourist activities in national parks. The authors show that in the context of a pandemic, the development of tourist activities in national parks is important for a positive image of these objects. It should be recognized that there are various problems with the development of tourist activities in national parks, the most important of which is the creation of infrastructure, as well as the development of sanitary and hygienic units on the main roads of republican, local significance and highways leading to tourist attractions. Research problem. Despite the fact that the country has great potential, Kazakhstan is not ready to meet the needs of foreign and domestic tourists due to some reasons. Kazakhstan took 80th place in the cumulative rating of the competitiveness of tourism and travel among 140 countries of the world in 2019, and in terms of tourism infrastructure, 89th place (World Economic Forum, 2020). Purpose of the study. Show and substantiate the possibilities for Tourism development in national parks of Kazakhstan. Research methods. Publications of domestic and foreign researchers, Internet resources have become the basis of the scientific method of analysis, theoretical and methodological concepts associated with the problems of Tourism Development in natural parks. The data for the study were taken from statistical data, in particular, from the database from the Official Statistics Authorities, to determine the monitoring of the flow of tourists. The regulatory framework for the study was the current regulatory legal acts, etc. Conclusions. Kazakhstan should realize that the country has a huge natural wealth, these are broad-leaved forests, lakes, a large number of rivers, great mountains, endless steppe, in addition, there are amazing and unusual plants and animals. It is necessary to be able to assess and use the capabilities of the country and try to effectively use the country’s resources. This can allow an increase in inbound tourist flow, an increase in the region’s prosperity, an increase in employment, the economic profit of the region and the country as a whole. National parks are necessary to maintain a favorable environment for the life of people. Observance of a healthy environment in national parks provides an opportunity to show the development of society in harmony with nature. The territory of the national park is the place where a person can get acquainted with the values ​​of wild nature, understand the spiritual values ​​of his or her country and all mankind. Thus, after analyzing the state national parks of Kazakhstan, it is advisable to make the most of the beautiful spaces of the national park for the development of tourist activities. To do this, first of all, we need high-quality infrastructure, assistance from the Public and Private partners, compliance with all rules and requirements both on the part of visitors and on the part of the organizer of the tourist facility. Key words: Natural parks, Tourism, Pandemic, State